PH-Sensing Characteristics of Hydrothermal Al-Doped ZnO Nanostructures. (21st October 2013) - Wang, Jyh-Liang; Yang, Po-Yu; Hsieh, Tsang-Yen; Hwang, Chuan-Chou; Juang, Miin-Horng
Abstract : Highly sensitive and stable pH-sensing properties of an extended-gate field-effect transistor (EGFET) based on the aluminum-doped ZnO (AZO) nanostructures have been demonstrated. The AZO nanostructures with different Al concentrations were synthesized on AZO/glass substrate via a simple hydrothermal growth method at 85°C. The AZO sensing nanostructures were connected with the metal-oxide-semiconductor field-effect transistor (MOSFET). Afterwards, the current-voltage ( I-V ) characteristics and the sensing properties of the pH-EGFET sensors were obtained in different buffer solutions, respectively. As a result, the pH-sensing characteristics of AZO nanostructured pH-EGFET sensors with Al dosage of 3 at.% can exhibit the higher sensitivity of 57.95 mV/pH, the larger linearity of 0.9998, the smaller deviation of 0.023 in linearity, the lower drift rate of 1.27 mV/hour, and the lower threshold voltage of 1.32 V with a wider sensing range (pH 1 pH 13). Hence, the outstanding stability and durability of AZO nanostructured ionic EGFET sensors are attractive for the electrochemical application of flexible and disposable biosensor.